A Novel End Effector for Telemanipulated Suturing in Robot-Assisted Laparoscopy - Kirst Alexander; Hellings-Kuß Anja; Hagmann Katharina; Dyck Michael; Schlenk Christopher; Klodmann Julian (Current Directions in Biomedical Engineering)
Suturing is an integral part of surgery. Specialized instrumentation facilitates manual needle handling to support laparoscopic suturing tasks, e.g. uterine closure, in minimally invasive surgery. Current solutions for robotassisted laparoscopy lack the possibility to integrate these instruments, making them suitable only for conventional laparoscopic surgery. This paper introduces a novel end effector design actuating a conventional suturing instrument. The end effector is integrated into the DLR MiroSurge system to facilitate telemanipulated suturing. The mechanical properties of the end effector are characterized and its feasibility for use in robot-assisted laparoscopy is demonstrated.